Metabolites from the mangrove-derived fungus xylaria cubensis PSU-MA34 - Saranyoo Klaiklay (2018)
Two new succinic acid derivatives, xylacinic acids A (1) and B (2), along with seven known compounds, including one succinic acid derivative (3), three mellein derivatives (4-6), cytochalasin D (7), 2-chloro-5-methoxy-3- methylcyclohexa-2,5-diene-1,4-dione (8) and isosclerone (9), were isolated from the mangrove-derived fungus Xylaria cubensis PSU-MA34. Their structures were established by spectroscopic evidence. They were evaluated for cytotoxicity against KB cells and antibacterial activity against Staphylococcus aureus ATCC 25923 and methicillin- resistant S. aureus.